Aplikasi Pupuk NPK melalui Sistem Infus Akar pada Tanaman Karet (Hevea brasiliensis) - Irmawati Irmawati; D P Priadi; Marlina Marlina; E Sodikin; M Ria; C R Amelia (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Irmawati I, Priadi DP, Marlina M, Sodikin E, Ria M, Amelia CR. 2022. The application of NPK fertilizer through root infuse system on rubber plant (Hevea brasiliensis). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 793-799. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The application of fertilizer with an infuse system is one alternative to increase the efficiency of fertilization on rubber plants. Root infuse systems are considered advantageous because of the reduced risk of fertilizer loss due to leaching and evaporation. For this reason, this study was conducted to determine the efficiency of NPK absorption through a root infuse system in rubber plants (Hevea brasiliensis). The research was carried out from September to December 2020 at the ATC rubber plantation, Faculty of Agriculture, Sriwijaya University. This study used a randomized block design with 4 treatments consisting of N0 = control, N1 = 80 grams of NPK per plant, N2 = 100 grams of NPK per plant, N3 = 120 grams of NPK per plant. The observed variables included the volume of absorbed solution, leaf greenness level, and NPK content in plant leaves. Based on the results, it was concluded that NPK fertilization using root infuse system on rubber plants had a significant effect on the variables of the volume of absorbed solution at 3rd and 4th weeks, and leaf greenness level. The higher the concentration of solution, the slower and less solution was absorbed by the plant.